Prof. Anuj Chauhan: contact lenses as the future of glaucoma treatment - Yu, Tan-Lun (Annals of Eye Science, 2018)
Prof. Anuj Chauhan (Figure 1) is a professor of Chemical Engineering at the University of Florida, USA. He was born and raised in India and moved to the United States to receive his Ph.D. degree in Chemical Engineering at the City University of New York. He completed his postdoctoral degree at the University of California, Berkeley. His areas of expertise include tear film dynamics, ophthalmic drug delivery, contact lenses, drug detoxification and microfluidics.